2021
DOI: 10.1002/adma.202008645
|View full text |Cite
|
Sign up to set email alerts
|

2D Honeycomb‐Kagome Polymer Tandem as Effective Metal‐Free Photocatalysts for Water Splitting

Abstract: On the basis of first‐principles calculations, the potential of applying 2D honeycomb‐kagome polymers made of heteroatom‐centered triangulene derivatives to photocatalyze water splitting is explored. The designed 2D polymers possess indirect bandgaps in the range of 1.80–2.84 eV and show pronounced light absorption in the ultraviolet and visible region of the solar spectrum. With suitable band edge alignment, the examined N‐ and B‐center polymers can generate sufficient photon‐excited electrons and holes to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 55 publications
2
72
1
Order By: Relevance
“…Following the previous reports, 46–48 we finally calculate the Gibbs free energy profiles of the OER and HER involved in photocatalytic water splitting on the GaSe and β-SnS surfaces, respectively. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the previous reports, 46–48 we finally calculate the Gibbs free energy profiles of the OER and HER involved in photocatalytic water splitting on the GaSe and β-SnS surfaces, respectively. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To address the photocatalytic water splitting, the Gibbs free energy profiles of the OER and HER processes on the GaSe and β-SnS surfaces, respectively, are calculated by adopting the method from previous reports, 46–48 see the ESI †…”
Section: Computational Model and Methodsmentioning
confidence: 99%
“…A further check of the electronic and optical properties indicated that altering the heteroatoms and bridge groups effectively adjusts the band edges and enhances light absorption (Box 1). As a result, the appropriate band edge alignment (Figure 3i) and good light absorption capability (Figure 3j) render 2D HTpolymers potential photocatalysts for HER or OER processes, respectively [65]. We have further demonstrated that the electronic properties of 2D polymers are determined by their lattice topology (Figure 3b) and the honeycomb-kagome lattice contributes to single-band features of 2D HT-polymers.…”
Section: Designing Principles Of 2d Conjugated Polymers For Photocata...mentioning
confidence: 72%
“…However, the combined impact of pH value to the performance of photocatalysts is complex, not limited to its additional effects on the thermodynamics of HER and OER [67]. Many theoretical studies only evaluated the photocatalytic activity of 2D polymers without considering the effect of different pH conditions [27,65].…”
Section: State-of-the-art Computational Approaches To Reveal Activiti...mentioning
confidence: 99%
“…[25][26] The unique attributes of COFs, including high crystallinity, tunable pore size, large specific surface area, and high chemical and thermal stability make them promising candidates for photocatalysis. [27][28][29][30][31][32] Very recently, layer-stacked COFs with impressive hydrogen evolution activities were reported, such as azine-linked N3-COF and cyanovinylene-linked sp 2 c-COF, and it was shown that functionalization of sp 2 c-COF with electron-withdrawing end groups further increased the hydrogen production rate. 18,22 Despite the rapid experimental progress, [33][34][35][36][37][38][39][40] few works reported the STH energy conversion efficiency of above 1%.…”
Section: Introductionmentioning
confidence: 99%